2014
DOI: 10.1055/s-0034-1390165
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Abdominal Flap for Unilateral Breast Reconstruction

Abstract: Use of this flap poses a greater challenge to the microsurgical breast reconstruction. We demonstrate its reliable use in women deemed unsuitable for a single-pedicle flap. Our structured system clarifies vascular options, and preoperative perforator mapping tools are essential to the success of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(49 reference statements)
0
6
2
5
Order By: Relevance
“…The safety of this reconstructive modality is well described, but its impact on additional revision surgery still remains unclear. 36–43 While others found no difference or a decreased incidence of revision when comparing patients undergoing bipedicle versus unipedicle reconstruction, the present study demonstrates an association between bipedicle reconstruction and more revision procedures. 43–45 Salibian et al demonstrated that the revision rate was higher in unipedicle reconstruction patients secondary to an increased rate of contralateral reduction.…”
Section: Discussioncontrasting
confidence: 47%
“…The safety of this reconstructive modality is well described, but its impact on additional revision surgery still remains unclear. 36–43 While others found no difference or a decreased incidence of revision when comparing patients undergoing bipedicle versus unipedicle reconstruction, the present study demonstrates an association between bipedicle reconstruction and more revision procedures. 43–45 Salibian et al demonstrated that the revision rate was higher in unipedicle reconstruction patients secondary to an increased rate of contralateral reduction.…”
Section: Discussioncontrasting
confidence: 47%
“…16 If the superficial vein is present in the flap but there is no second adequate recipient vein, it is suggested that an "intraflap" anastomosis connecting the superficial vein to the deep pedicle of the flap itself be created, thus allowing both to drain into a common recipient vein. [17][18][19] In the present study, the incidence of fat necrosis in the flap was lower in the dual venous drainage system group than in the single venous drainage system group when evaluated both in the physical exam alone (9.37% vs. 1.36%) and in the imaging exams (29.6% vs. 23.94%).…”
Section: Discussioncontrasting
confidence: 41%
“…Therefore, in many cases, it was necessary to do only one flap at a time. When both complementary flaps are able to be performed during the same operative procedure, the second flap can be anastomosed to the first one in series, in the same manner as described for stacked flaps in mammary reconstruction 13–15 …”
Section: Discussionmentioning
confidence: 99%